Industry Type and Accounting Numbers Relevance: The Case of Jordan - Shamki, Dhiaa; Bamahros, Hasan Mohammed (Asian Journal of Social Sciences and Management Studies, 2016)
The paper examines the impact of industry type on the accounting numbers relevance regarding three measures for security price known as average security price, closing security price and after three months security price for Jordanian service and manufacturing sectors within 2004-2013. Three regression models are used with and without control variables. The outcomes of the pooled sample are used in evaluating our hypotheses to reveal which security price is the most dependable. Influenced by the industry type, the relevance of book value regarding the three security measures and that of earnings regarding closing security price are greater in services sector than that in manufacturing sector. Cash flows are irrelevant regarding the three security measures. Our results reveal that closing security price is the most dependable in detecting the value relevance of the accounting numbers. Taking our findings in consideration could enable market participants to better extract the firm’s value through the type of industry that they invest in. Our conclusions regarding the importance of book value is supported by many studies making it being new evidence related to Jordan as one of the Middle Eastern region.